Multiparametric MRI and [18F]Fluorodeoxyglucose Positron Emission Tomography Imaging Is a Potential Prognostic Imaging Biomarker in Recurrent Glioblastoma - Hassanzadeh, Comron; Rao, Yuan James; Chundury, Anupama; Rowe, Jackson; Ponisio, Maria Rosana; Sharma, Akash; Miller-Thomas, Michelle; Tsien, Christina I.; Ippolito, Joseph E. (Frontiers in Oncology, 2017)
Purpose/Objectives: Multi-parametric advanced MR and FDG-PET imaging may be important biomarkers for prognosis as well for distinguishing recurrent glioblastoma (GBM) from treatment-related changes. Methods/Materials: We retrospectively evaluated 30 patients treated with chemoradiation for GBM and underwent advanced MR and FDG-PET for confirmation of tumor progression. Multi-parametric MRI and FDG-PET imaging metrics were evaluated for their association with 6-month overall (OS) and progression-free survival (PFS) based on pathological, radiographic, and clinical criteria. Results: 17 males and 13 females were treated between 2001- 2014, and later underwent FDG-PET at suspected recurrence. Baseline FDG-PET and MRI imaging was obtained at a median of 7.5 months (IQR 3.7-12.4) following completion of chemoradiation. Median follow-up after FDG-PET imaging was 10 months (IQR 7.2-13.0). Receiver-operator curve (ROC) analysis identified that lesions characterized by a ratio of the SUVmax to the normal contralateral brain (SUVmax/NB index) >1.5 and mean apparent diffusion coefficient (ADC) value of ≤1400 x10^-6 mm^2/s correlated with worse 6-month OS and PFS. We defined three patient groups that predicted the probability of tumor progression: SUVmax/NB index >1.5 and ADC ≤1400 x10^-6 mm^2/s defined high-risk patients (n=7), SUVmax/NB index ≤1.5 and ADC >1400 x10^-6 mm^2/s defined low-risk patients (n=11), and intermediate-risk (n=12) defined the remainder of the patients. Median OS following the time of the FDG-PET scan for the low, intermediate, and high risk groups were 23.5, 10.5 and 3.8 months (p<0.01). Median PFS were 10.0, 4.4, and 1.9 months (p=0.03). Rates of progression at 6-months in the low, intermediate, and high-risk groups were 36%, 67%, and 86%. (p=0.04) Conclusion: Recurrent GBM in the molecular era is associated with highly variable outcomes. Multi-parametric MR and FDG-PET biomarkers may provide a clinically-relevant, non-invasive and cost-effective method of predicting prognosis and improving clinical decision making in the treatment of patients with suspected tumor recurrence.